ANALISIS SENYAWA BIOAKTIF DAN AKTIVITAS ANTIOKSIDAN EKSTRAK BAWANG PUTIH (Allium Sativum L.) PROBOLINGGO - Lailatul Wakhidah; Mirwa Adiprahara Anggarani (Unesa Journal of Chemistry, 2021)
Garlic is a plant from the Allium genus which is found in the mountainous area of Probolinggo. The potensial bioactive content of this local product has not been studied to be developed in the development of garlic product diversification. This study aims to see the bioactive components, phenol content, flavonoid levels, and antioxidant activity in Probolinggo garlic tubers. The method in this research is divided into two parts, namely the extraction process and sample testing. The extraction process uses a multilevel method with three kinds of solvents, namely dichloromethane (non polar), ethyl acetate (semi polar), and ethanol (polar). The sample tests carried out included analysis of bioactive compounds, phenol levels using the Folin Ciocalteu method, flavonoid levels using the AlCl3 method, and antioxidant activity using the DPPH method. The results of the research on Probolinggo garlic tuber extract with dichloromethane and ethyl acetate solvents containing bioactive steroids and triterpenoids, while ethanol solvent contains bioactive compounds of flavonoids, saponins, steroids, triterpenoids and phenolics. Garlic tuber extract with ethanol solvent has a total phenolic value of 28,756 mg GAE / g and total flavonoids of 21,601 mg QE / g. The IC50 values ​​in the extracts of dichloromethane, ethyl acetate, and ethanol were 421.9643 µg / mL, 310.5998 µg / mL, 257.7503 µg / mL, respectively. In terms of the components of flavonoids, saponins, steroids, triterpenoids and phenolic, garlic tuber extract has a very weak antioxidant activity value. Keywords : garlic tubers, bioactive compounds, antioxidant activity.